Mapping Competitive Advantage in Competitive Markets: Analysis on the Creative Industry Sector in Southeast Asia - Fatmawati, Fatmawati; Nurbayani, Sri Undai; Isma, Andika; Alisyahbana, Andi Naila Quin Azisah; Diarra, Salim (PT Mattawang Mediatama Solution, 2025)
This study conducts a ten-year systematic mapping of competitive advantage within Southeast Asia’s creative industries, synthesizing insights from interdisciplinary literature to identify the key drivers shaping competitiveness in the region. The findings reveal that competitive advantage has shifted from traditional determinants toward an integrated model driven primarily by digital capability, innovation dynamics, and ecosystem support. Digital capability emerges as the most influential factor, enabling firms to enhance visibility, accelerate market reach, and adapt to rapidly changing platform environments. Innovation capability and dynamic organizational competencies further strengthen long-term competitiveness by facilitating continuous renewal, creative experimentation, and strategic resource reconfiguration. The analysis also highlights the central role of ecosystem governance, particularly public policy, infrastructure readiness, and institutional coordination in shaping industry performance. Countries with well-developed creative ecosystems, such as Singapore and Malaysia, demonstrate higher innovation maturity and digital integration, while others rely more heavily on community-driven or informal creative clusters. Platform-based competition and the rise of creator-led economies introduce new logics of value creation, emphasizing algorithmic mastery, content interactivity, and community engagement as key competitive mechanisms. Sustainability and cultural differentiation play equally significant roles, as creative firms increasingly integrate ethical practices, cultural authenticity, and collaborative partnerships to strengthen long-term relevance. Overall, the study concludes that competitive advantages in Southeast Asia’s creative industries is formed through the synergy of digital capability, innovation, ecosystem structures, cultural assets, and sustainability. These findings underscore the need for targeted policies, regional collaboration, and strategic digital development to position Southeast Asia as a globally competitive creative hub.